The Branding Impact on Charity Product Marketing Communication - Hilarius Bambang Winarko; Lawrence Sa Benning; Sri Tunggul Pannindriya (Research Center and Case Clearing House PPM School of Management, 2021)
This study aims to fill the research gap on millennials purchase attitude toward charity product in Youth of Indonesia (YoI) brand shoes which is promoted through social media. The research objective is to understand how branding elements affect the purchase intention of YoI shoes by using quantitative research method. There were 222 millennial valid respondents who are living in Jakarta metropolitan area participated in this research. The five brand elements are used as independent variables; they are brand awareness, perceived quality, brand association, brand loyalty, and brand credibility. Based-on the multiple linear regression output, it reports that brand awareness, perceived quality, and brand association do not have significant impact toward the millennials purchase intention. However, the brand loyalty and brand credibility give positive significant impact. Among others, the brand credibility is the most important factor that influence the millennials purchase intention as well as marketing communication strategy of this charity product.